CONSIDERING NEWBORNS OF MOTHERS POST-CERCLADAS - Haro S., Ángel (2015)
A comparative study of Newborns of mothers who have been subjected to cervical cerclage by isthmic-cervical incompetence is performed for the first time. 50 case histories of Newborn post higher banding normal deliveries, that serve as control group were taken. Newborns exception of multiple births, malformations and desconicimiento evident last menstrual period. The perinatal mortality was not excluded.